Live Longer, Work Longer: The Changing Nature of the Labour Market for Older Workers in OECD Countries - John P. Martin (Institute of Labor Economics (IZA), 2018)
Population ageing poses stark dilemmas for labour markets, social protection systems and cultural norms. It will put strong downward pressure on labour supply, leading to falling real incomes and huge financial pressures on social protection systems unless there is an offsetting increase in employment rates. This is especially true for older workers whose employment rates are well below those of prime-age adults. In this paper, I examine how the labour market for older workers has evolved in OECD countries since 1990, what are the main forces at work, what are the main obstacles to working longer and how might public policies help overcome them. I also speculate about the future for older workers faced with the challenges and opportunities posed by the gig economy.
Keywords: J08; J18; J21; J23; 330; population ageing; older workers; retention and hiring rates; ageism; seniority pay; gig economy